First Order Nonlinear Neutral Delay Differential Equations - Baghdad Science Journal (مجلة بغداد للعلوم)
The author obtain results on the asymptotic behavior of the nonoscillatory solutions of first order nonlinear neutral differential equations. Keywords. Neutral differential equations, Oscillatory and Nonoscillatory solutions.